Land Characteristics Impact Productivity and Quality of Ginger (Zingiber officinale Rosc) in Java, Indonesia - Nur Azizah; Sri Lestari Purnamaningsih; Sisca Fajriani (AGRIVITA, Journal of Agricultural Science, 2019)
Environmental condition plays an important on ginger production and its quality especially gingerol. Ginger exploration from various environmental conditions was carried out to obtain collection of ginger accessions that potentially developed as superior quality planting material. The study was aimed to assess the productivity and quality of gingers from different topography. The explorations of ginger accession was conducted in low-mid land and upland  area within Java island, Indonesia from June to August 2018. A total of 24 ginger accessions were collected, consisting of 11 big white ginger, 8 small white ginger, and 5 red ginger. Differences in environment condition (i.e topography) affected ginger productivity and gingerol content. The highest productivity of ginger for big white ginger, red and small white ginger were 32, 15 and 23 t/ha, respectively. The gingerol content was higher in red ginger (4-5%) than big white (3-4%) and small white (1%) gingers. However, there were two accessions of small white ginger contained gingerol above the average accessions of small white ginger, as well as higher than big white (4%) and red gingers (6%). Overall, land characteristics controlled yield and diameter of ginger rhizome through soil properties both chemical (e.g CEC) and physical (e.g soil texture).